Transformation of the administrative and legal status of cybercrime countermeasures entities - Korzun, Svitlana (Public Policy and Accounting, 2024)
Cybercrime is becoming increasingly widespread and complex, causing significant harm to both individual citizens and national security. This requires constant improvement of countermeasure mechanisms. The formation and development of a new configuration of state bodies responsible for countering cybercrime is crucial for the effective definition of state criminal policy in this area. The subject structure of the state policy to counter cybercrime is defined as follows: central executive bodies that implement the state criminal law policy to counter cybercrime; law enforcement entities that are entrusted with the functions of countering cybercrime that are directly related to countering cybercrime; law enforcement entities that are entrusted with the functions of countering cybercrime that are indirectly related to countering cybercrime. To determine the role of subjects of state policy to combat cybercrime in the implementation of the policy under study, the article analyzed regulatory documents regarding their administrative and legal status and powers. In the process of the study, directions for expanding the tasks and powers of subjects implementing state policy in the following areas were identified: ensuring economic security, financial monitoring, international cooperation in the field of information security; protection of critical infrastructure; law enforcement activities. The author proposed directions for expanding the subject structure of the law enforcement system in combating cybercrime, in terms of creating the National Bureau of Investigation of Cybercrimes and ensuring cyber security, as well as defining its tasks and powers, and formed directions for interaction with other subjects implementing the law enforcement function.